Aneuploidy Detection and mtDNA Quantification in Bovine Embryos with Different Cleavage Onset Using a Next-Generation Sequencing-Based Protocol - Hornak, Miroslav; Kubicek, David; Broz, Petr; Hulinska, Pavlina; Hanzalova, Katerina; Griffin, Darren; Machatkova, Marie; Rubes, Jiri (Cytogenetic and genome research, 2016)
Bovine embryos are now routinely used in agricultural systems as a means of disseminating superior genetics worldwide, ultimately with the aim of feeding an ever-growing population. Further investigations, common for human IVF embryos, thus have priority to improve cattle IVF, as has screening for aneuploidy (abnormal chromosome number). Although the incidence and consequences of aneuploidy are well documented in human preimplantation embryos, they are less well known for the embryos of other animals. To address this, we assessed aneuploidy levels in thirty-one 2-cell bovine embryos derived from early- and late-cleaving zygotes. Contemporary approaches ( Whole Genome Amplification and next-generation sequencing) allowed aneuploidy assessment for all chromosomes in oocytes from donors aged 4-7 years. We also quantified mitochondrial DNA (mtDNA) levels in all blastomeres assessed, thereby testing the hypothesis that they are related to levels of aneuploidy. The overall incidence of aneuploidy in this cohort of bovine embryos was 41.1% and correlated significantly with the timing of cleavage (77.8% in late-cleaving vs. 31.8% in early-cleaving embryos). Moreover, based on mtDNA sequence read counts, we observed that the median mtDNA quantity is significantly lower in late-cleaving embryos. These findings further reinforce the use of the bovine system as a model for human IVF studies.
Keywords: blastomery; Cattle; buněčné dělení; Animals; skot; Female; Embryo, Mammalian; aneuploidie; fertilizace in vitro; DNA, Mitochondrial; ženské pohlaví; Time Factors; časové faktory; Blastomeres; Male; mitochondriální DNA; Sequence Analysis, DNA; zvířata; cytokineze; mužské pohlaví; sekvenční analýza DNA; Aneuploidy; Cell Division; Cytokinesis; embryo savčí; Fertilization in Vitro